2018
DOI: 10.3390/su10041222
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Stakeholder Perceptions of Fish Decline: Making Sense of Multiple Mental Models

Abstract: Abstract:Stakeholders have different educational backgrounds, personal experiences and priorities that contribute to different perceptions about what causes natural resource decline and how to sustain a resource. Yet stakeholders have a common interest, which is to keep the resource of interest from declining. Effective co-management requires sharing of perceptions pertaining to the sustainability of a resource and making decisions that benefit all stakeholders. Therefore, this study used modified causal netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Increased similarity in perceptions of the most serious threats to the GBR across stakeholder groups in 2017 suggests that GBR managers may be better situated to develop management strategies likely to receive broad‐based support (Horowitz et al. 2018). Our findings also suggest which strategies are likely to work well in public communication because they are directed toward threats that resonate with the majority of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased similarity in perceptions of the most serious threats to the GBR across stakeholder groups in 2017 suggests that GBR managers may be better situated to develop management strategies likely to receive broad‐based support (Horowitz et al. 2018). Our findings also suggest which strategies are likely to work well in public communication because they are directed toward threats that resonate with the majority of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Shared perceptions within the community can help practitioners identify joint management goals and reduce disagreement among stakeholder groups that potentially hold dissimilar knowledge and values (Sutton & Tobin 2009;de Nooy 2013). Increased similarity in perceptions of the most serious threats to the GBR across stakeholder groups in 2017 suggests that GBR managers may be better situated to develop management strategies likely to receive broad-based support (Horowitz et al 2018). Our findings also suggest which strategies are likely to work well in public communication because they are directed toward threats that resonate with the majority of stakeholders.…”
Section: Convergence Of Threat Perceptions Within the Communitymentioning
confidence: 99%
“…Despite this superb work on erosion of forest governance in the literature on mountain regions and Uttarakhand's VPs in the HKH specifically, less is documented about the perceptions of change co-occurring among local forest stewards, diversity across attributed drivers of change, and associated responses. Several scholars have called for closer examination of heterogeneity within local natural resource management (e.g., Horowitz et al, 2018; van den Broek, 2018) and engagement with environmental perceptions as an important evidentiary basis for decision making on conservation (Bennett, 2016; Reyes-Garcia et al, 2019). Case studies across various sectors, from biodiversity conservation (e.g., Boubekri et al, 2023; Dencer-Brown et al, 2018) and agriculture (Below et al, 2015; Carmichael et al, 2023) to the effects of glacier recession (Gagne et al, 2014), have demonstrated the value of these insights for enriching understanding of social-ecological systems.…”
Section: Theorizing Environmental Change In the Hindu Kush Himalayamentioning
confidence: 99%
“…Incoming information is held up against our personal mental model, and we are predisposed to accept or reject the information based on how well it fits in with our understanding. There is extensive literature exploring methods for eliciting mental models and documenting the mental models of resource users (see, for example, Zaksek and Arvai 2004;Biggs et al 2011;Gray et al 2015;Horowitz et al 2018;Moon et al 2019), and an understanding of the mental models held by people can be critical for effective communication.…”
Section: Mental Models: What Are They?mentioning
confidence: 99%